Definition of the Elachista puplesisi Sruoga complex (Lepidoptera, Gelechioidea, Elachistidae), with description of a new species - Kaila, Lauri; Sruoga, Virginijus (Zootaxa, 2014)
The Elachista puplesisi group is defined. Its characterization is based on two species, E. puplesisi Sruoga, 2000, known from the holotype collected in Turkmenistan and E. helia sp. nov., from Rhodos, Greece. The group is assigned to the subgenus Atachia of Elachista, but its affinities within Atachia remain unknown.